Shades of Grey: How do Informal Firms Navigate Between Macro and Meso Institutional Environments? - De Castro, Julio O.; Khavul, Susanna; Bruton, Garry D. (Strategic Entrepreneurship Journal, 2014)
Our qualitative research shows that when making decisions about informality, entrepreneurs in emerging economies purposefully navigate between the enabling and constraining rules of the macro institutional environment and the norms of the meso institutional environment. We show that: (1) informality is a multidimensional continuum along which path to formalization unfolds; (2) as entrepreneurs grow more successful they become simultaneously more attuned to the countervailing constraints of both the macro and meso institutional environments; and (3) informal firms and formal firms weave together an exchange system that legitimizes the persistence of informality. In the context of informality, meso institutions serve as the connective tissue which cross‐link levels of the environment and shape the context in which entrepreneurs make decisions. Copyright © 2014 Strategic Management Society.